Tinjauan Hukum Islam Terhadap Tradisi Minum Cuka Dalam Pesta Pernikahan di Desa Ulak Tano Kec. Simangambat Kab. Padang Lawas Utara - Asnia Harahap & Ikhwanuddin Harahap & Syapar Alim Siregar (IAIN Padangsidimpuan, 2020)
The writing of this thesis is the background that the people of Ulak Tano Village carry out a habit / tradition of drinking vinegar in a wedding that will be held. This research raises the problem formulation, namely, How is the Tradition of Drinking Vinegar in a Wedding Party in Ulak Tano Village, Simangambat District, Kab. Padang Lawas Utara, How is the review of Islamic law on drinking vinegar at a wedding in Ulak Tano Village, Kec. Simangambat Kab. North Padang Lawas. So that the purpose of this study is to determine the tradition of drinking vinegar in a wedding party in Ulak Tano Village, Simangambat District, Kab. Padang Lawas Utara, to find out a review of Islamic law on the tradition of drinking vinegar at a wedding in Ulak Tano Village, Simangambat District, Kab. North Padang Lawas.